Materials Processing In Magnetic Fields - Proceedings Of The International Workshop On Materials Analysis And Processing In Magnetic Fields. - Schneider-Muntau, Hans J. (World Scientific, 2005)
Processing in magnetic fields is a rapidly expanding research area with a wide range of promising applications in materials science, development and design. Numerous research centers dedicated to materials research and processing in magnetic fields have been created around the world. This volume brings together contributions from these centers to review the most recent activities in this field. The papers in this book cover a broad spectrum of research of the effects on magnetic fields in materials processing. The cutting-edge research topics include magnetic levitation of diamagnetic matter a.